PERAN EVENT DALAM MENINGKATKAN CITRA DESTINASI PARIWISATA KOTA JAKARTA (STUDI KASUS PADA FESTIVAL #INIJAKARTA 2022 DI KOTA TUA JAKARTA) - Kallista Kallista; Roozana Maria Ritonga (LPPM Institut Pendidikan Nusantara Global, 2023)
Jakarta Old Town as one of the icons of Jakarta's tourism destinations which has just been revitalized in August 2022 is starting to be enlivened with various activities to increase the number of tourists and the destination image. One of them is the #IniJakarta 2022 Festival event which is being held by Plus Jakarta and The Ministry of Tourism and Creative Economy. This study aims to analyze the role of the #IniJakarta 2022 Festival event in enhancing the image of Jakarta Old Town tourism destination. This research method uses descriptive qualitative research. The research was conducted by interview, observation, and documentation. Data analysis includes four stages, namely data collection, data reduction, data display, and conclusion drawing. The results of the study found that the #IniJakarta 2022 Festival event increased the public awareness of Jakarta Old Town’s event and entertainment destination image. There are three supporting and inhibiting factors of the event. The role of the #IniJakarta 2022 Festival event in improving the image of Jakarta Old Town tourism destination is considered to have contributed enough in promoting and providing an overview of Jakarta Old Town which has been revitalized as a third space, but its role has not been maximized in terms of the social environment.